(untitled) (The Review of Diabetic Studies, 2025)
Background: Patient satisfaction is a key indicator of healthcare quality and is influenced by multiple factors across different healthcare sectors. Understanding the impact of health service factors on patient satisfaction can inform strategies to enhance care delivery, particularly in nursing, pharmacy, and public health services. Objective: This systematic review aims to examine the health service factors that influence patient satisfaction across healthcare sectors, with a focus on nursing, pharmacy, and public health services, highlighting common determinants and sector-specific challenges. Methods: A systematic literature search was conducted across databases including PubMed, Scopus, and Web of Science for studies published between 2010 and 2025. Studies reporting factors affecting patient satisfaction in nursing, pharmacy, or public health services were included. Data extraction focused on service delivery characteristics, healthcare provider interactions, accessibility, communication, and organizational factors. The quality of included studies was assessed using standardized appraisal tools. Results: A total of 68 studies met the inclusion criteria. Key factors influencing patient satisfaction included effective communication, responsiveness of healthcare staff, availability of resources, accessibility of services, patient-centered care approaches, and coordination among healthcare providers. Sector-specific findings indicated that in nursing, interpersonal skills and empathy significantly impacted satisfaction; in pharmacy services, medication counseling and timely dispensing were critical; and in public health services, accessibility and health promotion activities were primary determinants. Organizational and systemic factors, such as staff workload, waiting times, and infrastructure, also played a significant role across all sectors. Conclusion: Patient satisfaction is multifactorial and influenced by both provider-level and system-level factors. Enhancing communication, service efficiency, and patient-centered approaches across nursing, pharmacy, and public health services can substantially improve satisfaction. Policymakers and healthcare managers should prioritize integrated strategies addressing both human and structural aspects of care to optimize patient experiences.